Tradisi dan Solidaritas sebagai Problem Filsafat Sosial: Aṣabiyah Ibn Khaldūn dan Etika Keutamaan Alasdair MacIntyre - Ircham Nurfansyah; Qusthan Abqary Hisan Firdaus; Hanafi Hanafi (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2026)
This article compares Ibn Khaldūn’s concept of aṣabiyah and Alasdair MacIntyre’s virtue ethics in explaining the foundations of tradition and communal solidarity. This library-based study employs a comparative hermeneutical reading of al-Muqaddimah and After Virtue through description, interpretation, juxtaposition, and comparison. The findings demonstrate that both thinkers reject abstract individualism and regard concrete communal bonds as constitutive of identity and social life. Nevertheless, Ibn Khaldūn explains aṣabiyah at a macro-historical level as a force that produces political authority and sustains civilizational cycles. MacIntyre, by contrast, understands practices, virtues, the narrative unity of life, and tradition as normative foundations for character formation within communities. This article argues that their ideas cannot be synthesized into a single theory. They are better understood as a complementary dialogue: Ibn Khaldūn illuminates the structural-historical conditions of solidarity, while MacIntyre explains the formation of moral commitments sustaining it from within communal life.